Effect of the potassium iodide in tetrapropyl ammonium iodide-polyvinyl alcohol based gel polymer electrolyte for dye-sensitized solar cells - Mohd Abid, Mohd Asyadi Azam; Abdul Aziz, Mohd Fareezuan; Buraidah, Mohd Hamdi; Mohd Arof, Abdul Kariem (Elsevier GmbH, 2021)
Low ionic conductivity in gel polymer electrolytes with large cations is undoubtedly a critical issue. This research’s main objective was to explore potassium iodide influences on the conductivity in gel polymer electrolytes. PVA-based gel polymer electrolytes (GPEs), including tetrapropyl ammonium iodide and potassium iodide have been prepared. The GPEs have been characterized by X-ray diffraction (XRD) and electrical impedance spectroscopy (EIS). The GPEs prepared haves been recognized as an amorphous region through the X-ray diffraction analysis. The GPE sample’s conductivity (100 wt% of tetrapropyl ammonium iodide) of 6.24 × 10− 3 S cm− 1 was the lowest. The existence of potassium iodide in the GPE system improves the conductivity. The conductivity of 9.72 × 10− 3 S cm− 1 of GPE containing 30 wt% of tetrapropyl ammonium iodide and 70 wt% of potassium iodide was the highest derived from the EIS analysis. All prepared GPEs have the potential to be used for dye-sensitized solar cell applications. The dye sensitized solar cell efficiency has been improved by ~30% if potassium iodide exists in the GPE system.